Morphometric analysis of Hofbauer cells in normal placenta and chorioamnionitis in humans - Tauber, Zdenek; Foltynkova, Tereza; Cizkova, Katerina (Anatomia, Histologia, Embryologia, 2021)
Hofbauer cells are macrophages residing in the stroma of placental villi and play a number of roles during normal pregnancy, as well as pathological conditions. A morphometric analysis of Hofbauer cells, in particular to investigate the number of cells, their size and shape in samples of normal human placenta from 1st trimester, term and with chorioamnionitis was performed. Tissue samples were immunostained for CD206 antigen and evaluated using ImageJ software. We detected significant changes in number and morphology of HBCs between normal placenta and placenta with chorioamnionitis samples. In chorioamnionitis, the cells were unevenly distributed within the villi, generally present in higher numbers, larger and more elongated than those in normal 1st trimester and term placenta.
Keywords: makrofágy; Macrophages; chorioamnionitida; placenta; ženské pohlaví; Chorionic Villi; zvířata; Humans; Chorioamnionitis; Placenta; Female; Pregnancy; choriové klky; těhotenství; lidé; Animals